Characterization of coir/pineapple leaf fibre- reinforced polylactic acid hybrid composites for potential food tray applications - Siakeng, Ramengmawii (2018)
Natural fibre based polymer composites have been widely studied to substitute synthetic materials due to their multiple advantages such as availability, sustainability and biodegradable properties and low cost. The idea of this research is hybridising coir fibres (CF) and pineapple leaf fibres (PALF) into poly lactic acid (PLA) to make biodegradable composites for food packaging applications. The effects of alkali (6%), calcium hydroxide (6%) and silane (2%) treatment on the mechanical, morphological, and structural properties of CF and PALF were studied with the aim to improve their compatibility with PLA matrix. The findings show the overall properties with 6% alkali treatment were compatible with PLA matrix. Mechanical, structural, physical and thermal properties of untreated CF/PALF/PLA hybrid biocomposites were investigated on 30% fibre loading with different ratios of both fibres. It was observed that PALF have better effect on tensile and flexural properties while CF seems to enhance impact strength of the biocomposites and C1P1 biocomposites showed highest mechanical strength. Physical properties such as density, water absorption (WA), and thickness swelling (TS) of biocomposites were analyzed and obtained results indicated that C3P7 had the least density while C1P1 showed least TS. In thermal and dynamic analysis, C1P1 displayed highest degradation temperature and storage modulus while C7P3 revealed least coefficient of thermal expansion (CTE). Overall, the hybridisation effect in CIP1 hybrid biocomposites was the best in untreated biocomposites. Alkali treatment showed significant effects on physical, mechanical and thermal properties of biocomposites. Treated C3P7 hybrid biocomposites showed best tensile properties while treated C1P1 showed highest flexural and impact strength. In case of physical tests, all treated hybrid biocomposites showed lower WA and TS than untreated biocomposites. In TGA, treated biocomposites showed improve degradation temperature and increase weight loss excluding C3P7A. Treated C1P1 revealed the highest storage modulus in DMA. It was reported that the CTE of all the treated hybrid biocomposites displays lower values against untreated hybrid biocomposites and treated C1P1 shows least CTE. The biodegradability level of biocomposites were characterised by simple burial test (ASTM D570-98) through weight loss (%) of the samples after 30, 60, 90, 120 and 150 day’s soil burial and changes in physical and visuals in case of accelerated weathering test in accordance with ASTM G 154-16. Except for neat PLA, which shows almost no weight loss, all the biocomposites shows weight loss and were gradually degraded with time. The percentage weight loss in all the biocomposites was linear with number of days of soil burial. Untreated biocomposites shows higher/faster degradation compared to alkali treated biocomposites attributed may be due to poor fibre matrix adhesion, leading to fastening of degradation. Accelerated weathering tests reconfirm the degradation patterns which were also recorded by image analyser. The weathered samples shows increase surface roughness and change in colours due to the reaction with moisture, UV and humidity in the accelerated weathering chamber. Treated C1P1 hybrid biocomposites showed outstanding overall properties among all hybrid biocomposites and it is suitable for required light density, fair mechanical strength with good biodegradability and is suitable for potential food tray application.